Effectiveness of Legal Protection for Auction Winners in Land Disputes With Guaranteed Objects of Mortgage - Prabowo, Hertanto Adi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the Effectiveness of Legal Protection for Auction Winners in Land Disputes with Mortgage Guaranteed Objects in Banjarnegara Regency, to find out and analyze how the validity of the process of blocking property rights certificates that have been won through auctions in the concept of legal certainty, to find out and analyze how legal protection is for creditors and auction winners for blocking certificates of ownership rights, to find out and analyze examples of Deeds for Granting Mortgage Rights. The approach method in this study uses a sociological juridical approach. The specification of this study uses a sociological juridical approach. The specification of this research uses descriptive analytical research. The type of data used in this study is data from primary legal materials which include the Civil Code, the Mortgage Act No. 4 of 1996, BAL no. 5 of 1960, Minister of Finance No. 27/PMK.06/2016 Concerning Instructions for Implementation of Tenders, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 13 of 2017, Minister of Agrarian Regulation No. 3 of 1997 concerning Provisions for the Implementation of Government Regulation No. 24 of 1997 concerning Land Registration, Supreme Court Jurisprudence, SEMA No. 589/PAN.2/251/P/09/SK.Perd, as well as data on secondary legal materials from books and supporting documents. The data analysis method that the writer uses is qualitative data analysis. The results of the study show that the validity of the process of blocking SHM that has been won through an auction process is not legally valid and cannot be implemented because the ownership of the certificate of ownership has been transferred to the creditor with a promise to provide collateral in the form of the certificate of ownership to the creditor. Legal protection for auction winners for blocking SHM is contained in the Civil Code, Vendu Reglement, HIR, PMK Number 27/PMK.06/2016, and Supreme Court Judgment Jurisprudence.Keywords: Blocking; Legality; Mortgage; Protection.